ANALISIS KESELAMATAN DAN KESEHATAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN (ULP) WUA-WUA - Aminudin; Adelia Julia Sitorus; Sahrun (Halu Oleo University, 2025)
The purpose of this study was to determine occupational safety and health in improving employee performance at PT. PLN (Persero) ULP Wua-Wua. Research conducted using qualitative description research. The source of this research amounted to 5 people who were determined by using observation, interview and documentation techniques, namely the technique of determining informants who collected data directly in the field. The results of this study indicate that occupational safety and health at PT. PLN (Persero) ULP Wua-Wua shows that occupational safety and health has not been monitored optimally because there are still work accidents at PT. PLN (Persero) ULP Wua-Wua occur because the executor’s negligence does not check first or the job supervisor does not monitor because the procedure has been made Working Permit, JSA and has been surveyed in the field. In employee performance is an individual thing because each employee has a different level of ability in doing their job. Management can measure employee performance from each employee. Performnce depends on a combination of ability, effort and opportunity obtained.